Design and Implementation of a Non-Invasive Blood Sugar Monitoring System Using Infrared Optical Sensing Technology (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2025)
Diabetes is an increasingly prevalent health concern that significantly contributes to renal and cardiovascular diseases. Consequently, effective diabetes management necessitates consistent monitoring of glucose levels. One promising technological advancement in this area is the development of non-invasive glucometer monitoring. This study focuses on creating a user-friendly glucose monitoring system based on near-infrared sensors, which correlates variations in sensor output voltage with glucose concentrations, thereby facilitating accurate and convenient glucose monitoring for diabetes management. The primary goal is to assess the system's accuracy in comparison to traditional fingerstick methods and to evaluate its performance across various age demographics and dietary conditions through experimental testing and Clarke grid analysis. Our research introduces a non-invasive glucose monitoring technique utilizing near-infrared sensors, designed to be user-friendly. The experimental framework and prototype system have been developed to measure glucose level variations in relation to sensor output voltage. By applying Beer-Lambert's law, we established a correlation between light absorbance properties and sample concentration levels. Testing was conducted on individuals of different ages under various dietary conditions. The results obtained were systematically recorded and validated against the traditional fingerstick method, achieving an accuracy rate of 97.8%. Additionally, Clarke grid analysis was performed to illustrate the patterns observed.